The comparison of the pennation angle of knee extensor muscles in young women with pronated foot posture and normal ones - Zinat Ashnagar; Mohammad-Reza Hadian; Rahimeh Mahmoodi (Tehran University Medical Journal, 2023)
Background: Foot posture is proposed as an important factor that may affect the lower limb alignment. Variations from the normal foot posture may contribute to musculoskeletal injuries of the lower extremity especially knee joint. Considering variations in foot posture and knee joint alignment, this study aimed to assess and compare pennation angles of the vastus medialis oblique (VMO), vastus medialis (VM) and vastus lateralis (VL) in women with pronated foot posture and normal ones. Methods: This observational, case-control study was carried out on 31 women with pronated foot posture (foot posture index: 6-12) and 31 women with normal foot posture (foot posture index: 0-5) in the age range of 18 to 35 years old.  Participants were recruited from female students of university communities using Non-probability Sampling method. Sampling was carried out from September 2019 up to February 2020 at the biomechanics laboratory of rehabilitation faculty of Tehran University of Medical Sciences. The pennation angle of VMO, VM and VL muscles was measured by using two dimensional. B-mode ultrasound imaging (USI) .A 7.5MHz linear transducer with 50mm footprint was used for the measurements. The ultrasound images were analyzed using Image J software. Three longitudinal scans were captured for each muscle pennation angle while the probe removed between each scan. Results: The results of this study showed that there is no statistical significant difference between the pennation angles of  VMO, VM and VL in women’s foot posture compare to the normal ones (P>0.05). However, the results of intraclass correlation coefficient (ICC) of USI measurements showed “good” intrarater reliability for VMO (ICC=0.88), VM (ICC=0.87) and VL (ICC= 0.77) pennation angles. Conclusion: Based on the results of this study, the pennation angle of knee extensor muscles (VMO, VM, and VL), which was measured in non-weight bearing, is not different in young women with pronated foot compared to the normal ones. In addition, USI demonstrated good reliability for measuring VMO, VM and VL pennation angles.